Redesigning of the Basketball Training Simulator Machine By DFMA Method - Sor, Jun Kang; Mohd Amri Lajis, (Progress in Engineering Application and Technology, 2024)
The research consists of the DFA analysis and DFM analysis of the original design of the basketball training simulator machine and the improved basketball training simulator machine by using the Design for Manufacturing and Assembly (DFMA) method has been purposed. DFMA is a technique to reduce and minimize the time of assembly, cost, and number of parts on the existing product. Basketball Training Simulator Machine has become a very important piece of basketball equipment to the players and the coach for their basketball training section. In this research, the redesign of the basketball training simulator machine was done using the DFMA method to reduce the manufacturing cost and increase the design efficiency. At the same time, the cost analysis will be done also to analyze the manufacturing cost of the basketball training simulator machine before and after the redesign. The key for this research is to compare the original design of the basketball training simulator machine and the improved basketball training simulator machine which has superlative design efficiency and reduced cost of manufacturing. The manual assembly is determined by remodeling the existing model in SolidWorks 2018 software for the basketball training simulator machine. The original design has 14.26% of the design efficiency. After the improvement, the design efficiency of the improved design increased from 14.26% to 28.74% which increased by 14.48%. There have been 3 modifications made to improve the basketball training simulator machine. The total reduction part is reduced by 136 parts from 231 parts on the original design to 95 parts on the improved design. From the DFM analysis, the results show that the total manufacturing cost of the design is RM 2225.83, but the total manufacturing cost of the improved design is RM 2050.05. The total manufacturing cost decreased by RM 175.78. Results from total absorption cost show that the original design of the basketball training simulator machine is estimated at RM 2226.93 while the improved design cost is around RM 2051.26. There were RM175.67 cost reductions between these two models.